Association Between Payment Scheme, Insurance Participation, and Economic Status with Orthodontic Appliance Preference in West Jakarta - Hanarni Kubelinda; Joko Kusnoto; Lia Hapsari Andayani; Budi Kusnoto (Journal of Indonesian Dental Association, 2026)
Introduction: The primary goals of orthodontic treatment are to improve mastication function and tooth alignment. The choice of orthodontic appliance type can be influenced by various factors such as treatment payment plans and economic status. Objective: To determine the association between payment scheme, insurance participation, and economic status with orthodontic appliance preference among undergraduate students in West Jakarta. Methods: This cross-sectional study involved 158 undergraduate students in West Jakarta, taken by purposive sampling. Data collection was conducted using a questionnaire in September 2025. The questionnaire was distributed via Google Forms and consisted of eighteen questions. The Fisher's Exact test was used to examine the association between payment scheme, insurance participation, and economic status with orthodontic appliance preference. Results: Fixed orthodontic appliances were chosen by the majority of respondents (88%), with orthodontic specialists fitting the appliances (61.4%). Non-installment payment was the most popular payment method (85.4%), with 65.2% of respondents spending IDR 10,000,000 or more on treatment costs. The majority of respondents did not use insurance for orthodontic treatment (91.8%). There was a significant association between the father's income with orthodontic appliance preference (p= 0.018). Conclusion: Orthodontic appliance preference is associated with father's income. However, orthodontic appliance preference is not associated with payment schemes, insurance participation, parental education, parental occupation, or the mother's income. Collaboration between insurance companies and healthcare providers is needed to develop subsidy program towards orthodontic treatment.